2007
DOI: 10.3354/dao074027
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion and ejection of hooks: effects on long-term health and mortality of angler-caught yellowfin bream Acanthopagrus australis

Abstract: Ninety juvenile yellowfin bream Acanthopagrus australis were angled from holding tanks, allowed to ingest nickel-plated, carbon-steel J-hooks and released (with their lines cut) into individual experimental tanks during 2 experiments in order to assess their (1) long-term (up to 105 d) health, mortality and rate of hook ejection and (2) short-and medium-term (< 42 d) temporal changes in health during hook ingestion. Equal numbers of control fish were scooped from holding tanks and similarly monitored in experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 27 publications
3
44
0
Order By: Relevance
“…Compared with their larger conspecifics, smaller A. australis may have been less able to avoid tactile stressors during their capture in the beach seines. However, unlike Gerres subfasciatus, A. australis have hard scales, are physically robust and apparently quite resilient to a range of impacts with different fishing gears (Broadhurst et al 2005, 2007b, Uhlmann & Broadhurst 2007. While there were no concomitant, significant effects of TL on the mortality of Sillago ciliata, this may reflect their smaller sample size (i.e.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Compared with their larger conspecifics, smaller A. australis may have been less able to avoid tactile stressors during their capture in the beach seines. However, unlike Gerres subfasciatus, A. australis have hard scales, are physically robust and apparently quite resilient to a range of impacts with different fishing gears (Broadhurst et al 2005, 2007b, Uhlmann & Broadhurst 2007. While there were no concomitant, significant effects of TL on the mortality of Sillago ciliata, this may reflect their smaller sample size (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…seined-or gilled-and-discarded vs. controls) on the numbers surviving at the end of each experiment. The blood samples collected from confined and angled Acanthopagrus australis and Neoarius graeffei at the end of the monitoring periods were analysed for concentrations of plasma glucose (mmol l -1 ) to provide an index of acute stress (Mazeaud et al 1977, Grutter & Pankhurst 2000, Broadhurst et al 2007b. Glucose concentrations were derived by means of colorimetric clinical kits (Roche Diagnostics) using an enzymatic spectrophotometric assay done according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The long-term utility of this approach for minimizing negative impacts has been validated for yellowfin bream Butcher et al, 2010). In particular, Broadhurst et al (2007) observed a non-significant mortality of 15% for line-cut, hook-ingested fish over more than three months, with 76% of survivors ejecting their hooks after an average of 20 d while maintaining their overall condition. No similar data are available for snapper or mulloway, but during 3 d of monitoring, Grixti et al (2010) recorded 13% hook ejection by similarly treated snapper (n ¼ 59).…”
Section: Introductionmentioning
confidence: 98%
“…For some species, their morphology and feeding strategies are probably important (Aalbers et al, 2004;Broadhurst et al, 2007;McGrath et al, 2009). However, irrespective of biological traits, it is likely that both the mortality of fish and their hook ejection are strongly influenced by hook decay, mainly because this dictates how long the point and barb remain sharp (and the potential for associated internal damage), and overall structural integrity is maintained (Aalbers et al, 2004;Broadhurst et al, 2007). Recognition of the importance of hook decay precipitated a recent study by McGrath et al (in press) to isolate some of the key contributory technical factors.…”
Section: Introductionmentioning
confidence: 99%
“…The survival of these regulatory discards is unquantified but current management measures would only be effective in conserving stocks if released fish survive capture and subsequent release (Broadhurst et al, 2005a;Butcher et al, 2007Butcher et al, , 2008. The survival of discarded individuals represents a large source of uncertainty in estimates of total fishing mortality (Davis, 2002).…”
Section: Introductionmentioning
confidence: 99%